2001
DOI: 10.1200/jco.2001.19.10.2658
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Borderline Tumors With Particular Interest to Persistence, Recurrence, and Progression to Invasive Carcinoma: A Prospective Study

Abstract: PURPOSE: Borderline tumors account for 10% to 20% of epithelial ovarian tumors, and their prognosis is outstanding; nevertheless, a mortality of up to 20% has been reported, particularly in earlier reports. There is a lack of information about the actual mortality and the rate of progression into invasive carcinoma in large and prospectively accrued populations. PATIENTS AND METHODS: All women with borderline ovarian tumors undergoing primary surgery in our department or referred within 3 months from surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
256
5
33

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 375 publications
(312 citation statements)
references
References 21 publications
12
256
5
33
Order By: Relevance
“…However, both Hispanic and non-Hispanic Whites show an elevation in the pool of smoking-related cancers (Table 2) However, it is difficult to see how surveillance bias accounts for the histology of ovarian cancers following CCIS. We show that about 40% of such cases are borderline tumors of low malignant potential (Table 3), which is twice the prevalence in our comparison group(s) and higher than published estimates (10-20%) [29,30]. To be sure, this histologic finding is a statistical observation, but one that may call for a biologic investigation.…”
Section: Results Of the Case-control Studycontrasting
confidence: 44%
“…However, both Hispanic and non-Hispanic Whites show an elevation in the pool of smoking-related cancers (Table 2) However, it is difficult to see how surveillance bias accounts for the histology of ovarian cancers following CCIS. We show that about 40% of such cases are borderline tumors of low malignant potential (Table 3), which is twice the prevalence in our comparison group(s) and higher than published estimates (10-20%) [29,30]. To be sure, this histologic finding is a statistical observation, but one that may call for a biologic investigation.…”
Section: Results Of the Case-control Studycontrasting
confidence: 44%
“…In larger studies that focus on the assessment of fertility results in patients with all stage of disease, Gottlieb et al 4 reported three cases (two with Stage II and one Stage III disease) in patients with advanced stage, and Morris et al 5 three cases (with Stage III disease) 4,5 . Zanetta et al 17 have reported an important series of 399 patients with borderline tumour of whom 24 with peritoneal implants were treated conservatively 17 . However, the fertility results were not detailed 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the ACTION trial concluded that optimally staged early epithelial ovarian cancers patients do not benefit from the use of adjuvant chemotherapy [20,21] The conflicting results indicates that properly staged invasive ovarian cancer stage Ia should not receive adjuvant chemotherapy, but not properly staged stage Ia patients should undergo a thorough staging procedure in order to avoid adjuvant chemotherapy. Borderline tumors have a very low risk of recurrence and they rarely respond to chemotherapy or irradiation [22]. Thus, adjuvant treatment with chemotherapy or irradiation should not be offered patients with borderline tumors [9].…”
Section: Discussionmentioning
confidence: 99%